Sexual Scripts and the Sexual Behavior of Men and Women Who Use Pornography. (20th October 2016) - Bridges, Ana J.; Sun, Chyng F.; Ezzell, Matthew B.; Johnson, Jennifer
Using data collected from 1, 880 heterosexual men and women residing in the United States, this study investigated the associations among gender, pornography consumption, and 20 sexual behaviors observed in popular pornography. Acts were grouped according to whether participants reported engaging or being interested in trying specific sexual behaviors as the (a) aggressor (e.g., hairpulling, spanking, or choking), (b) target (e.g., being spanked or choked), or (c) uncommon and/or degrading sexual activity (e.g., male ejaculation in female partner's mouth, anal sex, double penetration, and ass-to-mouth). Using sexual script theory, we hypothesized greater use of pornography would be associated with greater likelihood of both having engaged in and interest in engaging in these sexual behaviors. We further hypothesized gender differences consistent with pornographic sexual scripts that frequently portray men as aggressors and women as targets of aggression. Hierarchical multiple regressions revealed significant main effects for gender and pornography use on the three categories of sexual behavior but no significant interactions. Higher pornography use was associated with greater likelihood of both engaging and being interested in trying all categories of sexual behavior. Men were more likely than women to have engaged in aggressive and degrading/uncommon behaviors, and women were more likely than men to have engaged in target behaviors. However, men were more interested than women in trying all three categories of sexual behavior. Results provide partial support for sexual script theory; while higher pornography use increased interest and prior engagement in pornography-like sexual behavior, the increases in types of sexual behavior (aggressor, target, or uncommon/degrading) were not moderated by gender.